Expanding the Foundation for Personalized Medicine: Implications and Challenges for Dentistry - Garcia, I. (J Dent Res, 2013)
Personalized medicine aims to individualize care based on a person’s unique genetic, environmental, and clinical profile. Dentists and physicians have long recognized variations between and among patients, and have customized care based on each individual’s health history, environment, and behavior. However, the sequencing of the human genome in 2003 and breakthroughs in regenerative medicine, imaging, and computer science redefined “personalized medicine” as clinical care that takes advantage of new molecular tools to facilitate highly precise health care based on an individual’s unique genomic and molecular characteristics. Major investments in science bring a new urgency toward realizing the promise of personalized medicine; yet, many challenges stand in the way. In this article, we present an overview of the opportunities and challenges that influence the oral health community’s full participation in personalized medicine. We highlight selected research advances that are solidifying the foundation of personalized oral health care, elaborate on their impact on dentistry, and explore obstacles toward their adoption into practice. It is our view that now is the time for oral health professionals, educators, students, researchers, and patients to engage fully in preparations for the arrival of personalized medicine as a means to provide quality, customized, and effective oral health care for all.